Thyroid imbalance and hypothyroidism: A review - Hasan, Afrida; Hasan, Md. Rabby; Jafreen, Rehnuma (International Journal of Public Health Excellence (IJPHE), 2024)
Hypothyroidism, which occurs when the thyroid gland in the neck is unable to produce enough thyroid hormone to fulfill the body's demands, is one of the most common disorders in the world. This can lead to heart problems, infertility, and poor brain development in infants. A person's quality of life may be impacted by hypothyroidism if they have depressed symptoms, weariness, weakness, and weight fluctuations. An inadequate consumption of iodine through diet is the main cause of hypothyroidism in developing countries. Therefore, iodizing salt is a common approach made by many countries to increase iodine consumption. This review discuss about the gland, position, hormone, features of hypothyroidism.